Causes of delays in government sector project: a case study of Power Grid Company of Bangladesh (PGCB) Ltd. - Hasan, Md. Mahmudul (BRAC University, 2019)
This dissertation is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2018.